Pancasila as the Identity of the State: The Pillar of Nationalism and National Integration - Citra, Dian Ananda; Amelia, Amelia (PT. Civil Military Center, 2025)
Pancasila, as the foundation of the state and the worldview of the Indonesian nation, has served as a collective identity that unites Indonesia’s diversity since the proclamation of independence. Throughout its journey, Pancasila has played a fundamental role in fostering national consciousness, preserving state integrity, and providing policy direction that supports national development. This article aims to analyze how Pancasila remains increasingly relevant as the identity of the state in the modern context by reinforcing its values in social and political life. Using a review of recent academic literature, this study examines the challenges and opportunities in applying Pancasila in the era of globalization, amid rapid social, political, and economic changes. The research employs a descriptive-qualitative method through a literature review encompassing books and scholarly journals published between 2020 and 2024. The analysis shows that strengthening Pancasila’s values is essential to address the challenges of modernization and globalization, which often threaten the nation’s identity. This article also recommends concrete strategies to integrate Pancasila values into national policies, the education system, and daily life to reinforce the state’s identity amid global transformation.